Cross-Linked Chondroitin Sulfate Adhesion Barrier System in Open Rectal Resection - Yukihide Kanemitsu; Eiji Hashizume; Takeshi Suto; Kazunori Yawata; Kenichi Inaoka; Kazuhiro Hiramatsu; Koji Komori; Masataka Ikeda; Nobuhiro Ishido; Masahiko Watanabe (JAMA Surgery, 2026)
Importance Adhesions commonly occur after abdominal and pelvic surgery, causing infertility, intestinal obstruction, and pelvic pain. Existing anti-adhesion materials are often difficult to use on uneven organ surfaces, highlighting the need for novel solutions; SI-449, a cross-linked, powder-formed chondroitin sulfate (CS), may address these limitations. Objective To evaluate the anti-adhesion effect of the SI-449 adhesion barrier system (cs barrier) in patients undergoing open rectal resection for rectal cancer. Design, Setting, and Participants This multicenter, prospective, randomized, open, and blinded–end point (PROBE) method pivotal clinical trial was conducted at 53 hospitals in Japan from September 2020 to June 2023. The study participants and efficacy assessors on the central review board were blinded. Patients aged 20 years or older with clinical stage I through IV rectal cancer who underwent open rectal resection and were scheduled for follow-up ileostomy closure were eligible for inclusion. Data were analyzed from July 2023 through September 2023. Intervention The control group received no additional procedure before abdominal closure, while the experimental group received 2 to 3 g of SI-449 applied to the abdominal or pelvic cavity immediately before closure. Main Outcomes and Measures The primary end point was the incidence of adhesions under the incision. Secondary end points included adhesion number, severity, and extent; number and type of adhered organs; and number of adhesions per organ. Safety and operability were also evaluated. Results Among 155 screened patients, 131 met the inclusion criteria and were randomized. Of these, 128 underwent the intervention (safety analysis population; control group: n = 64; experimental group: n = 64), and 118 completed a second surgery (modified intention-to-treat population; control group: n = 60; experimental group: n = 58). Overall mean (SD) patient age was 68.2 (10.3) years, and 34 patients of 118 (29%) were female. Adhesion incidence was significantly lower in the experimental group (26 of 58 [45%]) compared to the control group (56 of 60 [93%]) ( P < .001). The experimental group also showed significantly reduced adhesion severity and extent. No safety concerns were identified, and operability was good. Conclusions and Relevance In this randomized clinical trial, SI-449 in the powdered form reduced the incidence of adhesions, and the adhesion barrier system had good operability and no safety concerns. Thus, this system may provide a new anti-adhesion option for use in open surgery. Trial Registration jrct.mhlw.go.jp Identifier: jRCT1080225247